Waste minimization in the synthetic textile industry - Pongsri Paopuree; Samorn Muttamara; Yang, Byung-Soo; Sompol Boonthanon; Royal Thai Government (RTG) (Bangkok : Asian Institute of Technology, 1996)
A large scale synthetic textile industry was selected for waste minimization study. It was found that more than 88% of total water supply was consumed in dyeing process. The distribution of wastewater in nylon and polyester dyeing process were 36% and 48% respectively. Due to a large portion of wastewater discharged from textile industry in term of high COD, colour, BOD5, and alkalinity that actually cause the environmental problems. Waste minimization techniques can reduce the level of the threatening environmental problems, however, inevitably was found in dyeing process. This study was performed that the selected industry will be approached in waste minimization as following techniques. Firstly, source reduction by means of good house keeping and reducing the volume of wastewater in physico-chemical system by not combined colourless wastewater to coloured wastewater. Consequently the factory will save 2,000 baht/month. Secondly, there are two main on- site sources to reused water, the third scouring rinsing unit and polishing pond. From these two points the factory will save 10,000 baht/month and 4,000 baht/month, respectively. Thirdly, Iron salt no.1 which act as coagulant is necessary being substituted for Alum in physico-chemical system. Proper preconditioning operation in activated sludge system will gain higher efficiency, and factory will save more than 100,000 baht/month.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1996
Keywords: Waste minimization